2016
DOI: 10.1002/jez.b.22721
|View full text |Cite
|
Sign up to set email alerts
|

Gene Ages, Nomenclatures, and Functional Diversification of the Methuselah/Methuselah‐Like GPCR Family in Drosophila and Tribolium

Abstract: Affecting lifespan regulation and oxidative stress resistance, the G-protein coupled receptor (GPCR) gene methuselah (mth) plays important roles in the life history of Drosophila melanogaster. Substantial progress has been made in elucidating the molecular pathways by which mth affects these traits, yet conflicting ideas exist as to how old these genetic interactions are as well as how old the mth gene itself is. Root to these issues is the complex gene family history of the Mth/Mthl GPCR family, which experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…1B and Fig. S2B) (10,11), plus four genes encoding cell-surface proteins: SR-CIV (scavenger receptor protein); Pvr (PDGF/VEGF receptor tyrosine kinase); Oamb (octopamine Ca 2+ signaling/cAMP receptor), and Mthl10, an orphan GPCR (12). The Mthl10 hit was particularly striking: A high Z score mean of −4.6 was obtained from three separate dsRNA pairs ( Fig.…”
Section: Significancementioning
confidence: 97%
“…1B and Fig. S2B) (10,11), plus four genes encoding cell-surface proteins: SR-CIV (scavenger receptor protein); Pvr (PDGF/VEGF receptor tyrosine kinase); Oamb (octopamine Ca 2+ signaling/cAMP receptor), and Mthl10, an orphan GPCR (12). The Mthl10 hit was particularly striking: A high Z score mean of −4.6 was obtained from three separate dsRNA pairs ( Fig.…”
Section: Significancementioning
confidence: 97%
“…Previous studies showed that the mth gene is related to lifespan and stress resistance in D. melanogaster (Lin et al, 1998). D. melanogaster mthl10 is one of the paralogues of mth (Patel et al, 2012;Friedrich and Jones, 2017) which initiates PLC/Ca 2+ signalling to mediate immunological, metabolic and stressprotective responses and lifespan functions in response to the ligand growth-blocking peptide (GBP) (Sung et al, 2017). Recent research has revealed that 16 members of the Mth/Mthl gene family in D. melanogaster consists of both Mth ectodomain-positive and Mth ectodomainnegative members (Friedrich and Jones, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is also too early to rule out that, at least to some extent, lineage‐specific gene family loss in a broader ancestral panel of mth superclade GPCRs caused a selective survival of mth superclade GPCRs in modern Schizophora. However, the tens of millions of years of conservation of the large majority of mth superclade GPCRs, combined with their extensive diversification in the Mth ectodomain within the constraints of its conserved disulfide bond folding structure, continues to be highly indicative of a major adaptive gene family expansion (Friedrich & Jones, ).…”
Section: Discussionmentioning
confidence: 99%
“…The available data are also sufficient to conclude that parallel mth superclade expansions happened at different time points in different schizophoran lineages. The emergence of the melanogaster subgroup subclade, for instance, must have occurred later than the expansion of the newly identified calyptrate subclad e. Calyptrate Diptera have been estimated to date back 40–60 million years compared to the origin of the melanogaster subgroup, which has been estimated to have originated approximately 3 million years ago (Friedrich & Jones, ; Obbard et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation